Pengaruh penggunaan Media Trimino Matematika dalam tatanan model pembelajaran kooperatif terhadap hasil belajar matematika siswa kelas I SDN 034 Tarai Bangun Kecamatan Tambang Kabupaten Kampar - Jesi Alexander Alim; Syahrilfuddin Syahrilfuddin; Jalinus Jalinus (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2015)
This study aims to describe generally about the effects of using Trimino Mathematical Model of Cooperative Learning on the results of mathematics, especially for the first grade students of SDN Tarai Bangun. The method used is to analyze and interpret experiments clearly about the conditions that exist in the field. The data collection techniques used were direct observation of the experiment as the subject of research. The results of this study can be concluded that learning through trimino mathematical model cause differences improvement of students’ mathematics learning outcomes significantly between the experimental class and control class. The attitude of the students based on the scale of attitudes about learning initiative, set a goal of learning, motivation, behavior (self), find and utilize relevant learning resources, evaluate the process and outcomes of learning. This is indicated positively by the opinion of students towards learning mathematics using mathematical trimino media.